Uterine artery embolization: is it reliable for myoma treatment? - Dogan, Nurullah; Nas, Omer Fatih (The European Research Journal, 2017)
Objective. We aimed to share the long-term technical and clinical success results, complications and radiologic follow-up findings in our myoma cases treated with uterine artery embolization (UAE) ) and to make a contribution to the literature data on this subject. Method. The study was retrospective and the results of 70 patients who underwent UAE for myoma treatment at our institute between January 2012 and January 2015 were analyzed. Results. The age range was 22 to 46 years and the mean age 34 years. The postprocedural follow-up duration was 6 to 24 months and the mean follow-up duration was 14 months. The technical success rate was 100% and the clinical success rate was 84.7%. On postprocedural follow-up, fibroid passage was seen in 2 patients (2.85%), severe hypermenorrhea in 4 (5.7%) and postembolization syndrome in 6 (8.5%). Our myoma recurrence rate was 11.36% (n=5). The UAE procedure did not need to be repeated in any of the patients. Conclusions. UAE is a reliable alternative to hysterectomy and myomectomy. We believe that UAE should be preferred in patients who are recommended hysterectomy or are predicted to potentially need hysterectomy during myomectomy.